2019
DOI: 10.1007/s10198-019-01081-y
|View full text |Cite
|
Sign up to set email alerts
|

Partner’s depression and quality of life among older Europeans

Abstract: We aim to study among European older adults (after age 50) if partner's mental health influences the individual's well-being. A sample of married or with registered partnership couples that live together, from the latest wave of the Survey of Health, Ageing and Retirement in Europe (SHARE) is considered. More specifically, we use logistic regressions to determine the impact that partner's mental health has on an individual well-being. Besides, personal health and socio-demographic characteristics are also anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The current study proposed that female individuals are more likely to be affected by the depression symptoms of their spouses (Marguerite et al, 2017 ). Two studies reported that women are associated with lower quality of life compared to men when facing the mental health of their intimate partners (Maroufizadeh et al, 2018 ; Pascual-Sáez et al, 2019 ). One possible explanation is that women are socialized to be interdependent and more sensitive to mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The current study proposed that female individuals are more likely to be affected by the depression symptoms of their spouses (Marguerite et al, 2017 ). Two studies reported that women are associated with lower quality of life compared to men when facing the mental health of their intimate partners (Maroufizadeh et al, 2018 ; Pascual-Sáez et al, 2019 ). One possible explanation is that women are socialized to be interdependent and more sensitive to mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is not surprising that depression, a non-fatal disease, is gaining attention as a population health issue among researchers. In particular, late-life depression is an important public health problem due to its association with multiple negative health outcomes, including mortality (Blazer, 2005 ; Fiske etal., 2009 ; Horackova et al, 2019 , Zhao et al, 2012 ) as well as overall poor quality of life, not only for the affected individuals but also for their partners and relatives (Pascual-Sáez et al, 2019 ). Understanding and analysing late-life health outcomes are becoming critically important, especially in the twenty-first century where individuals increasingly live longer lives.…”
Section: Introductionmentioning
confidence: 99%
“…Pascual‐Saez et al. (2019) perform a cross‐sectional analysis of the association between partners' mental health and individual well‐being for older Europeans using SHARE data and show that there are important spillover effects. However, this study does not consider the effect of unobserved individual and partner characteristics and the possibility that these traits may be driving the results.…”
Section: Literature Reviewmentioning
confidence: 99%